1998
DOI: 10.1002/pc.10156
|View full text |Cite
|
Sign up to set email alerts
|

Mold filling analysis in vacuum‐assisted resin transfer molding. Part II: SCRIMP based on grooves

Abstract: Compared with SCRIMP based on the high‐permeable medium, SCRIMP based on grooves has the advantage of a much higher mold filling rate. This paper analyzes the influences of various molding conditions on mold filling and presents models that can be used to predict the filling time and flow pattern in SCRIMP based on grooves. Mold filling experiments were carried out to investigate the effect of various factors such as the size of the groove, groove spacing, number of fiber layers and resin viscosity on mold fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 5 publications
1
30
0
Order By: Relevance
“…The experimental permeability of each specimen derived from the in-plane flowing experiments and the predictive permeability obtained from the fitting curves showed in Table 3. The diversity of predictive and experimental permeability in Table 3 almost below ±15% and the experiments with large diversity happened in thick laminates, such as (MD) × 4 + M and (MLT) × 5 + M, because the channel effect [8] easily occurred in the sides of thick laminates and affected the observation of flowing process. The permeability of single-type laminates with white dots and data of multi-type laminates with black dots on top and bottom surfaces displays in Figure 6(a) and Figure 6(b) respectively.…”
Section: Permeability Prediction Of Fiber Laminates With Single-type mentioning
confidence: 99%
See 3 more Smart Citations
“…The experimental permeability of each specimen derived from the in-plane flowing experiments and the predictive permeability obtained from the fitting curves showed in Table 3. The diversity of predictive and experimental permeability in Table 3 almost below ±15% and the experiments with large diversity happened in thick laminates, such as (MD) × 4 + M and (MLT) × 5 + M, because the channel effect [8] easily occurred in the sides of thick laminates and affected the observation of flowing process. The permeability of single-type laminates with white dots and data of multi-type laminates with black dots on top and bottom surfaces displays in Figure 6(a) and Figure 6(b) respectively.…”
Section: Permeability Prediction Of Fiber Laminates With Single-type mentioning
confidence: 99%
“…The VARTM simulation involves with parameters, such as the viscosity of resin, the porosity and permeability of fiber laminates. The permeability of FRP laminates is critical in the manufacturing process and numerous researchers have investigated the measurements and analytical models of permeability [7,8] [ [11][12][13][14][15]. Sun [7] and Ni [8] set up a device to visualize the experimental results and measurements of permeability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, a few studies about resin flow through sandwich composites can be found. Jun Ni et al (1998) studied the resin flow in a sandwich composite with a grooved core designed to speed up the mold filling process. An analytic model for unidirectional flow advancement in a sandwich composite with fibrous core was presented by Song and Youn (2007).…”
Section: Introductionmentioning
confidence: 99%